Estudo sobre fatores influentes nos resultados de ensaios não destrutivos em concreto endurecido - Ferreira, Gercindo (2011)
Significant contributions for the civil engineering has been providing by advanced technology with special distinction for the non destructive tests used in the structures of reinforced concrete. Usually, concrete strenght is the most appraised property, however, other characteristics, as the durability and the permeability have expressive importance for certain processes of evaluation. The non-destructive tests do not cause damage in concrete structures, therefore, do not generate loss resistant capacity. The objective of this work is show the results study of the influence that the variables: maximum characteristic dimension of coarse aggregates, the variation of humidity of concrete, layer concreting, distance between pulse ultrasonic transducers and reinforcing position exerts on the results of non-destructive testing of concrete, ultrasonic pulse velocity, sclerometry, resistivity and half-cell potentials, specifically. Concrete surface´s moisture, relative humidity and temperature are monitored. The variation of moisture in concrete was produced by controlled sprinkling water. The tests were conducted in 6 concrete blocks with 6 years of age and 10 reinforced concrete beams with 2 years of age. Weight proportion in the concrete was maintained in the blocks. DMA of coarse aggregates were 9.5 mm, 19 mm and 25 mm. By results of UPV concluded that blocks with largest DMA, the UPV was minor, the middle layer presented greater value of UPV, for blocks and beams the UPV has increased when the surface was sprinkled or the distance between the transducers increased. The smaller rebound index was on blocks containing aggregates with largest DMA and for blocks and beams occurs a decrease of rebound index as superficial moisture increases. The concrete´s resistivity only reducted after 1750 g/m2 of water surface wetting. The final average reduction was 24% to B1-B2 blocks, 15% to B3-B4 and none to B5-B6. The higher the DMA lower the reduction coefficient in the results. The measures of half-cell corrosion changed between the beams. However, a uniformity of behavior occurred in all elements, from the accumulated sprinkling of 500 g/m2 of water, with close values to the final.